Interventions for the treatment and prevention of pressure ulcers. (1st June 2022) - Hill, James Edward; Edney, Sarah; Hamer, Oliver; Williams, Alexandra; Harris, Catherine
Abstract : Pressure ulcers can affect multiple aspects of an individual's life. Though preventable, pressure ulcers place a substantial economic burden on healthcare services. Countries around the world have set pressure ulcer prevention and treatment as a high priority. National Clinical Guidelines recommend a wide range of preventative and curative treatments. However, there is still much uncertainty regarding the effectiveness of preventative and curative treatments. This overview of systematic reviews aims to describe the findings of 15 Cochrane reviews on the treatment and prevention of pressure ulcers included in a previous umbrella review and to expand upon their findings in the context of clinical practice.